Successful use of a phage endolysin for treatment of chronic pelvic pain syndrome/chronic bacterial prostatitis - Stevens, Roy H.; Zhang, Hongming; Kajsik, Michal; Płoski, Rafał; Rydzanicz, Malgorzata; Sabaka, Peter; Šutovský, Stanislav (Frontiers in Medicine, 2023)
Chronic prostatitis (CP) is a common inflammatory condition of the prostate that is estimated to effect 2-10% of the world's male population. It can manifest as perineal, suprapubic, or lower back pain and urinary symptoms occurring with either recurrent bacterial infection (chronic bacterial prostatitis [CBP]) or in the absence of evidence of bacterial infection (chronic pelvic pain syndrome [CPPS]). Here, in the case of a 39-yearold CBP patient, we report the first successful use of a bacteriophage-derived muralytic enzyme (endolysin) to treat and resolve the disease. Bacteriological analysis of the patient's prostatic secretion and semen samples revealed a chronic Enterococcus faecalis prostate infection, supporting a diagnosis of CBP. The patient's E. faecalis strain was resistant to several antibiotics and developed resistance to others during the course of treatment. Previous treatment with multiple courses of antibiotics, bacteriophages, probiotics, and immunologic stimulation had failed to achieve long term eradication of the infection or lasting mitigation of the symptoms. A cloned endolysin gene, encoded by E. faecalis bacteriophage Ef11, was expressed, and the resulting gene product was purified to electrophoretic homogeneity. A seven-day course of treatment with the endolysin resulted in the elimination of the E. faecalis infection to below culturally detectable levels, and the abatement of symptoms to near normal levels. Furthermore, during the endolysin treatment, the patient experienced no untoward reactions. The present report demonstrates the effectiveness of an endolysin as a novel modality in managing a recalcitrant infection that could not be controlled by conventional antibiotic therapy.